A new endophytic species, Diaporthe litseae, from medicinal plants in Guizhou Province, China - Sun, Ya-Ru; Liu, Ning-Guo; Al-Otibi, Fatimah O.; Hyde, Kevin D.; Jayawardena, Ruvishika S. (Phytotaxa, 2024)
During our study on microfungi associated with medicinal plants in China, a new endophytic taxon, Diaporthe litseae was isolated from healthy leaves of Litsea kobuskiana collected in Guizhou Province, China. The new species is characterized by its coelomycetous asexual morph, which has dark brown to black, globose conidiomata, cylindrical, aseptate conidiophores, phialidic conidiogenous cells, and fusiform, hyaline, aseptate, guttulate conidia. The phylogenetic analyses of combined ITS, tef1-α, β-tubulin, cal and his3 sequence data indicate D. litseae is phylogenetically distinct from other species. A detailed description and illustration for D. litseae are provided herein.